Refleksja w codzienności – perspektywa pedagogii osoby - Starnawski, Witold (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Common experience is the starting point in classical model of philosophy and in pedagogy as well. Everyday reality is a phenomenon of the human world and contains subjective components. The main elements of that phenomenon are: monotony, concreteness, directness, objectiveness, routine, automatism. Reflexion makes, that everyday events and processes change to environment of personal participation and activity. There are two type of reflexion: ontological and cognitive; both are important to create personal level of live. A man usually doesn’t recognize values in everyday reality, because of his lack of attention and too absorbing activity. The negative side of that reality is presented by the passivity or activism of the person and preference to stabilization customs and routine. The positive side – confirms realistic view, verifies his words, promises, declarations, gives firm foundation against subjectivism, doubts, uncertainty. Reflexion in everyday reality allows to recognize the deeper level of reality that is usually inaccessible to inattentive consciousness.
Keywords: common experience; everyday reality; monotony; pedagogy; person; reflexion; routine